"Preparing them for the profession": An interpretative phenomenological analysis of anatomy educators coping with complexity in the United Kingdom curriculum. Issue 2 (8th October 2022) - Kirkness, Karen B.; Bazira, Peter J.; Finn, Gabrielle M.; Nizza, Isabella E.
Abstract: Efforts to integrate the basic sciences into the ever‐changing curriculum are a trending area of research in health professions education. Low‐stakes, high‐frequency assessment methods such as the progress test are now widely implemented in the United Kingdom and Northern Ireland as a means of furthering curricular integration toward contemporary goals of competency and professional identity formation. The anatomy educator's experience vis‐à‐vis these curricular changes is not well understood. This study aimed to explore how anatomy educators make sense of the shifting demands of their role. The interviews were semi‐structured, particularly concerned with the phenomenon of teachers adapting to the complexity of their learning environment. The study used interpretative phenomenological analysis (IPA) to focus on the lived experiences of participants coping with the phenomena in question: how do anatomy educators make sense of the learning environment in the United Kingdom? Interviews were transcribed verbatim and interpreted inductively, identifying four key themes: confidence through connectedness, variations in appraisals of curricular integration, managing expectations to perform in paradoxical situations, and the emergence of innovative teaching. Results point to the learning environment as a complex system and highlight the importance of feeling support from and connection to colleagues, enabling individual educators to develop confidence, meet the top‐down demands of changing curricula, and experience personal identity development and uncertainty tolerance within their role. This IPA study offers insight into the lived experiences of anatomy educators whose experiential interpretations of a complex and changing curriculum can uniquely inform stakeholders in health professions education.